“NOT AVAILABLE FROM YOUR LOCATION”: CONTROL AT THE INTERSECTION OF GEOGRAPHY, TECHNOLOGY, AND POLICY – A CASE STUDY OF NETFLIX IN AUSTRALIA - Hentrich, Nicole (AoIR Selected Papers of Internet Research, 2015)
The relationship between media industries and technologies of media distribution is long-lived and pervasive. Central to this has been the nexus of the control of space and the control of various technological affordances that accompany new methods of media distribution and consumption. From publishing houses in the early days of the printing press attempting to limit “pass along-s” of books to Hollywood seeking to ban the VCR within domestic settings, the struggle between audience convenience and accessibility, and industry profit and control is ever-present. With the move to digital content and distribution, the television industry is in a state of flux both within the United States and around the world. Online streaming services are transforming not only how people watch television, but they are also pushing the academy and the industry to reconsider what television is. In general there is a disconnect between how streaming is discussed within the US academy and popular press and how it is being understood in other geographic locations. Whereas US conversations tend to centre on how online streaming and subscription services are changing television viewing habits, in non-US contexts the discussion hinges on questions of access. The process of geo-blocking content, and the ways in which viewers in geo-blocked locations access this content, has profound implications for the ways in which television is consumed in non-US context.